Optimalisasi Pemenuhan Hak Pendidikan dan Pembinaan Karakter Anak Berkonflik dengan Hukum: Studi Kasus LPKA Kelas II Bandar Lampung - Cici Dian Purnamasari; Rizqullah Nurwidya (Jurnal Sosial Humaniora dan Pendidikan, 2025)
This study evaluates the implementation of formal education rights fulfillment and character development programs for juveniles in conflict with the law at the Class II Juvenile Correctional Facility (LPKA) in Bandar Lampung, while identifying key challenges and optimization strategies. A descriptive qualitative approach was employed, with data collected through observation, in-depth interviews, and document analysis. The findings reveal that administrative constraints (incomplete identity documents), an insufficient educator-to-student ratio, limited facilities, and minimal family support significantly hinder access to and the quality of formal education, as reflected in low participation rates and graduation outcomes below the national average. Character development initiatives encompassing religious, physical, and vocational training positively contribute to moral strengthening, reduction in disciplinary violations, and enhanced readiness for social reintegration, although full participation remains limited. Recommendations include accelerating the issuance of administrative identity documents, increasing the capacity and number of educational personnel, providing technology-based learning facilities, fostering external partnerships, and strengthening family involvement. An integrated strategy is expected to enhance the effectiveness of rehabilitation efforts and reduce the risk of juvenile recidivism.